2015
DOI: 10.1039/c5ra03707g
|View full text |Cite
|
Sign up to set email alerts
|

Routes towards catalytically active TiO2doped porous cellulose

Abstract: Cellulose-TiO 2 nanocomposites have been successfully prepared by non-solvent induced phase separation, either from cellulose solutions in ionic liquids or from cellulose acetate solutions in classical organic solvents followed by deacetylation ("regeneration"). Commercially available titania nanoparticles from gas phase synthesis processes have been used and processed as dispersions in the respective polymer solution. The used TiO 2 nanoparticles have been characterized by means of transmission electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 27 publications
2
22
0
Order By: Relevance
“…[Emim][OAc] and [Bmim][OAc] water content was ≤1.1% according to supplier specification. Because in our previous works we had demonstrated that traces of water do not hinder cellulose solubilization and do not have a negative impact to the phase separation process, 45 all materials were used as received. Further on, we considered that this may also facilitate the up-scaling if desired.…”
Section: Methodsmentioning
confidence: 99%
“…[Emim][OAc] and [Bmim][OAc] water content was ≤1.1% according to supplier specification. Because in our previous works we had demonstrated that traces of water do not hinder cellulose solubilization and do not have a negative impact to the phase separation process, 45 all materials were used as received. Further on, we considered that this may also facilitate the up-scaling if desired.…”
Section: Methodsmentioning
confidence: 99%
“…The direct synthesis of titania anatase modification on reduced graphene oxide was reported where the applied IL‐anion directly coordinates to the titanium precursors resulting in a TiO 2 ‐RGO hybrid . Also, the incorporation of titania nanoparticles into cellulose‐based materials is facilitated by ILs , …”
Section: Il Based Synthesesmentioning
confidence: 99%
“…[83] Also, the incorporation of titania nanoparticles into cellulose-based materials is facilitated by ILs. [84,85] However, a more detailed study of these hybrid materials might exceed the scope of this review. Nevertheless, we are convinced that the potential of ILs in inorganic synthesis is not fully exploited yet and that the presented materials have al-REVIEW ready promising applications in the fields of gas sorption, photocatalysis, and battery application.…”
Section: Hybrid Materialsmentioning
confidence: 99%
“…Furthermore, cellulose is applicable for supporting TiO 2 nanoparticles owing to its good compatibility with TiO 2 nanoparticles. Several types of low-dimensional cellulose materials have been reported, including cellulose nanofibers and films by electrospinning and phase separation method, respectively [ 2 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%